Advancements in research on the anti-aging effects and mechanisms of flavonoids in natural products - Li, Wan-yu; Zhang, Liang; Xie, Xing-wen; Shi, Xiao-feng; Ma, Qu-huan (Frontiers in Medicine, 2025)
In recent years, with the continuous development of social productivity and improvements in living standards, the issue of population aging has intensified. As the elderly are susceptible to cardiovascular diseases, osteoporosis, Alzheimer’s disease, and other conditions, the economic and resource burdens associated with treating, caring for, and supporting this demographic rise with their growing numbers, imposing significant pressure on societal development. In light of these challenges, research on natural products possessing anti-aging properties for treating aging-related chronic diseases has gained prominence. Flavonoids, a class of natural bioactive compounds abundantly found in plants, exhibit diverse pharmacological effects, including antioxidant, anti-inflammatory, and anti-osteoporosis activities. Therefore, studying the anti-aging effects of flavonoids is of significant value. This paper reviews recent research on the anti-aging effects of flavonoids by searching databases including CNKI, PubMed, Web of Science, and Google Scholar. The findings are summarized based on research subjects (C. elegans, animal models, and cells), effects, and mechanisms, to provide references for future in-depth research on the anti-aging effects of flavonoids.